2018
DOI: 10.1016/j.molliq.2018.10.106
|View full text |Cite
|
Sign up to set email alerts
|

Environmental properties of phosphonium, imidazolium and ammonium cation-based ionic liquids as potential lubricant additives

Abstract: This research compares the environmental properties (bacterial toxicity and biodegradability) of 12 ionic liquids-ILs-(7 phosphonium, 2 imidazolium and 3 ammonium cation-based ones), potentially applicable as lubricant additive, with two types of the traditional lubricant additive ZDDP. Aquatic toxicity was determined by means of Vibrio fischeri and Escherichia coli bacteria, while biodegradability was evaluated through biological oxygen demand (BOD 5) and chemical oxygen demand (COD) measurements. Regarding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 105 publications
1
27
1
Order By: Relevance
“…Considering TU data, all these three [N8881] cation-based ILs can be classified as toxic (TU values from 1 to 10). It should be noted that, although it is included in the same category, the [N8881][TFSI] IL showed a value of TU around 4 times higher than those obtained for the ILs here studied [28]. A C C E P T E D M A N U S C R I P T a EC50 classification for aquatic life: non-toxic: EC50 > 100 mg/L; harmful (acute 3): EC50: 10 -100 mg/L; toxic (acute 2): EC50: 1 -10 mg/L; and very toxic (acute 1): EC50 < 1 mg/L.…”
Section: Based On Ghs (Globally Harmonized System Of Classification Acontrasting
confidence: 54%
See 4 more Smart Citations
“…Considering TU data, all these three [N8881] cation-based ILs can be classified as toxic (TU values from 1 to 10). It should be noted that, although it is included in the same category, the [N8881][TFSI] IL showed a value of TU around 4 times higher than those obtained for the ILs here studied [28]. A C C E P T E D M A N U S C R I P T a EC50 classification for aquatic life: non-toxic: EC50 > 100 mg/L; harmful (acute 3): EC50: 10 -100 mg/L; toxic (acute 2): EC50: 1 -10 mg/L; and very toxic (acute 1): EC50 < 1 mg/L.…”
Section: Based On Ghs (Globally Harmonized System Of Classification Acontrasting
confidence: 54%
“…The values of toxicity, expressed as EC50, for the ILs tested are shown in Table 5. Various authors have reported that the cationic part is the one which principally controlled toxicity [28,43,44]. Nevertheless, on viewing these data, it should be noted that the anionic part also had a considerable effect on toxicity.…”
Section: Bacterial Toxicity: Vibrio Fischeri Testsmentioning
confidence: 99%
See 3 more Smart Citations